IMPLEMENTING SHARIA ACCOUNTING PRINCIPLES IN THE PUBLIC SECTOR: A SYSTEMATIC LITERATURE REVIEW OF CHALLENGES AND OPPORTUNITIES - Chilshi, Indrya; Aini, Kuratul; Marina, Rani; Roja, Delga; Firdaus, Anhar; Arifai, Muhammad; Mariana, Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This study aims to systematically examine the challenges and opportunities in implementing Sharia accounting principles within the public sector. Using a Systematic Literature Review (SLR) approach, it analyzes scholarly publications addressing practices, barriers, and the potential of Sharia accounting adoption in government institutions. The findings indicate that research remains largely concentrated on religious nonprofit entities, while implementation in formal public institutions—such as local governments, ministries, and state-owned enterprises—remains limited. Key obstacles include low levels of understanding among personnel, insufficient regulatory frameworks, and the absence of Sharia-based accounting standards for the public sector. Yet, integrating Sharia principles can enhance both vertical and horizontal accountability and foster ethical public governance. Therefore, regulatory development, human resource training, and institutional strengthening are crucial for achieving effective and sustainable implementation.